Familial dilated cardiomyopathy: a worse prognosis compared with sporadic forms. Issue 2 (August 1995) - Csanády, M.; Högye, M.; Kallai, A.; Forster, T.; Szárazajtai, T.
Abstract : OBJECTIVE--To establish the time of onset of dilated cardiomyopathy (DCM) by review of annual chest x rays, which are obligatory in Hungary. DESIGN--A retrospective survey of chest x rays of a cohort of confirmed cases of DCM, to assess time of onset of cardiomegaly. Clinical course was compared by follow up over a mean of six years from the time of diagnosis. SUBJECTS--240 patients with DCM (31 familial, 209 non-familial). Diagnosis was made by echocardiography in all cases and confirmed by coronary angiography and heart biopsy in some cases. MAIN RESULTS--At diagnosis, the mean age of the patients was 31.8 years in the familial group and 39.6 years in the non-familial group (P < 0.05). The time between the onset of cardiomegaly (cardiothoracic ratio > 0.45) and clinical diagnosis was 8.0 and 10.1 years respectively (P < 0.05). The six year survival was 6% in the familial group and 23% in the non-familial group (P < 0.05). CONCLUSIONS--The familial form of DCM is the more malignant form: it occurs at an earlier age and progresses more rapidly than non-familial DCM.